Keys to the Costa Rican species of paper wasps (Hymenoptera: Vespidae: Polistinae) - Valverde, J.-Pablo (2019)
Paper wasps (subfamily Polistinae) are one of the four main groups of eusocial insects in the Neotropics. They are medically important for the frequent stings inflicted on humans, but at the same time are valuable predators of pest insects. Nonetheless, there are no updated keys for the identification of the Central American species. Here we provide keys to the 18 genera and 106 species known to occur in Costa Rica, illustrated with one hundred original line drawings.